2022
DOI: 10.3390/jcm11123477
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet: The Beneficial Effects of Lycopene in Non-Alcoholic Fatty Liver Disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) presents the most common chronic liver disease globally; it is estimated that 25.24% of the world’s population has NAFLD. NAFLD is a multi-factorial disease whose development involves various processes, such as insulin resistance, lipotoxicity, inflammation, cytokine imbalance, the activation of innate immunity, microbiota and environmental and genetic factors. Numerous clinical studies have shown that the Mediterranean diet produces beneficial effects in NAFLD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 86 publications
0
17
0
Order By: Relevance
“…In this study, the transcriptome combined with KEGG analysis further identified a significant regulatory role for lycopene in pathways associated with lipid metabolism, inflammation, fibrosis, and apoptosis. Particularly, there was pronounced enrichment in inflammation-related pathways, aligning with prior research demonstrating lycopene’s inflammation-reducing effects in organism induced by a HFD through ROS regulation . KEGG pathway analysis additionally revealed significant regulation of advanced glycation end products and TH17 cell differentiation, indicating the insulin resistance and immunomodulatory effects of lycopene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the transcriptome combined with KEGG analysis further identified a significant regulatory role for lycopene in pathways associated with lipid metabolism, inflammation, fibrosis, and apoptosis. Particularly, there was pronounced enrichment in inflammation-related pathways, aligning with prior research demonstrating lycopene’s inflammation-reducing effects in organism induced by a HFD through ROS regulation . KEGG pathway analysis additionally revealed significant regulation of advanced glycation end products and TH17 cell differentiation, indicating the insulin resistance and immunomodulatory effects of lycopene.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several phytochemicals exhibiting potential anti-inflammatory properties, such as curcumin, diosmetin, quercetin, and astaxanthin (a type of carotenoid), have emerged as promising candidates for NASH treatment. It is worth noting that some of these compounds have been reported to regulate the phosphorylation of ASK. , Lycopene, as a highly potent antioxidant carotenoid, possesses diverse pharmacological characteristics, including anti-inflammatory, antioxidant, and photoprotective effects. Its efficacy in controlling lipid metabolism has rendered it advantageous in the treatment of NAFLD. ,, Previous research has proven that a high intake of lycopene (12 mg/kg/day) can alleviate atherogenic high-fat-induced liver inflammation in a mouse model, including restoring dyslipidemia and hepatic dysfunction . The beneficial effects of lycopene are often attributed to its antioxidant stress; however, its underlying mechanisms for improving ER stress in the progression of NASH remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that lycopene can activate the essential signaling pathway in redox homeostasis (nuclear factor erythroid 2-related factor 2 pathway) to promote the expression of antioxidant genes, reduce oxidative stress, and repair liver damage [ 9 , 10 ]. Additionally, several preclinical and clinical studies have been conducted to validate the protective and preventive effects of lycopene on NAFLD [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…( 19 ). Some animal studies have reported LY supplementation ameliorated hepatic steatosis and decreased serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels in obese rodents ( 20 ), indicating the protective effect of LY on NAFLD. However, the potential mechanisms are largely unknown.…”
Section: Introductionmentioning
confidence: 99%